Chemistry experiments - Selectmedia Entertainment (Firm); OverDrive, Inc. ([South San Francisco, Calif.] : Selectmedia Entertainment, 2006)
Science fun at home! Want to know what makes things rust? How about which materials will dissolve in water? Or how to construct a model atom? With Kid science: Chemistry experiments, you can learn answers to these questions and more. Kid science makes learning about the elements that surround us easy and fun. Discover the amazing properties of solids, liquids and gases. Includes many fun and easy activities to try at home. Video demonstrations make chemistry experiments both interesting and safe. Learn about solutions, electrolysis, chromatography and more.
Downloadable video file.
Title from title screen (viewed on Nov. 21, 2006).
"Science fun at home!"--Graphic on title screen.
Ages 9 and up.
Also available as DVD.
Mode of access: World Wide Web.
Keywords: Chemistry -- Experiments -- Juvenile films; Instructional videos